Appraisal of harmful traditional practices in Nigeria: magnitude, justifications and interventions - Timilehin Olayinka Omoniyi (Journal of Social, Humanity, and Education, 2020)
Purpose: The study did an appraisal of harmful traditional practices (HTPs) in Nigeria despite global, regional, national laws, policies and programmes, women and girl-children are still being subjected to dehumanising treatments. Research methodology: Systematic search in literature, personal experiences, archival materials, and oral interviews were used in data collection, while thematic analysis was used to interpret oral confessions carried out on thirty-six (36) elderly persons who were purposively selected. Results: There is high prevalence of HTPs across the Nigeria which the cultural and secular laws are silent about. It was discovered that many children (underage 10-15years of age) in Hausa/Fulani lands are prone to marriage by adoption, force or early marriage of girls between, while in the Eastern part, the is high magnitude of child hustling, outrageous dowry payment, separatist theory as practiced in Osu caste system, servitude (Maid) etc, and in the West are practices of scarification, wife battery, polygamy. They rely on socio-cultural, psycho-sexual, spiritual and aesthetic justifications. The study recommends action-related studies followed by proper education interventions. Limitations: The study covered HTPs across Nigeria with 36 participants. Further studies should concentrate on tribe or region basis with larger participants. Contribution: This study did an appraisal of harmful traditional practices in Nigeria; magnitude, justifications and interventions Keywords: Harmful Traditional Practices, Traditions, Magnitude, Justification